Resistance to Hypoosmotic Shock of Liposomes Containing Novel Pigments from an Antarctic Bacterium - Blamey-Alegria, J (2012)
Although the antioxidant capacity of carotenoids and their role in regulating membrane fluidity have been well studied, their ability to confer resistance to hypoosmotic shock is poorly understood. In this work, we analyzed the effect of a mixture of carotenoid pigments obtained from an Antarctic microorganism belonging to the genus Pedobacter on liposomal resistance to hypoosmotic conditions. Intercalation of pigments into liposomal structures resulted in an improvement of membrane resistance by decreasing the percentage of calcein released in comparison to that by liposomes without pigments. Due to these properties, such pigments could be useful for biotechnological applications. © The Korean Society for Microbiology and Biotechnology.